Enjeux de la peine et efficacité socio-juridique, le cas du braconnage - Murbach, Ruth (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1987)
This note analyzes the perceptions and proceedings of judges and Crown prosecutors when they face a hardly known, decried and severely punished phenomenon: poaching. The findings of a qualitative research indicate that the means and procedures of game protection have unintended implications. The deterrent effect of mandatory minimum penalties is not obvious, while there is evidence that they burden unduly the administration of justice.